(untitled) (Journal of Engineering, 2017)
Taguchi experimental design (TED) is applied to find the optimum effectiveness of aqueous Red Pomegranate Peel (RPP) extract as a green inhibitor for the corrosion of mild steel in 2M H3PO4 solution. The Taguchi methodology has been used to study the effects of changing, temperature, RPP concentration and contact period, at three levels. Weight-loss measurements were designed by construction a L9 orthogonal arrangement of experiments. Results of the efficiencies of inhibition were embraced for the signal to noise proportion & investigation of variance (ANOVA). The results were further processed with a MINITAB-17 software package to find the optimal conditions for inhibitor usage. Second order polynomial model was used for experimental data fitting. Optimum conditions for achieving the maximum corrosion inhibition efficiency are obtained from optimizing the above model and are found as follow: 39.66 °C temperature of acidic media, 38.29 ml/L inhibitor concentration and 2.95 h contact period. Results demonstrated that rate of corrosion was increased with temperature increasing & decreasing inhibitor concentration. It was concluded that the Taguchi design was adequately useful in the optimization of operating parameters and that RPP sufficiently inhibited the corrosion of steel at the range of variables studied.